2020
DOI: 10.1128/aac.00900-20
|View full text |Cite
|
Sign up to set email alerts
|

Suramin Inhibits SARS-CoV-2 Infection in Cell Culture by Interfering with Early Steps of the Replication Cycle

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic that originated in Wuhan, China, in December 2019 has impacted public health, society, the global economy, and the daily lives of billions of people in an unprecedented manner. There are currently no specific registered antiviral drugs to treat or prevent SARS-CoV-2 infections. Therefore, drug repurposing would be the fastest route to provide at least a temporary solution while better, more specific drugs are being developed. Here, we de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 39 publications
(52 reference statements)
6
89
0
Order By: Relevance
“…Our GO clustering analyses detected clustering of great significance for annotations such as establishment of RNA localization, cell projection, lyase activity, cell cycle and more. These fall in line with the current literature which describes such disturbances upon SARS-CoV-2 infection 4042 and could also represent putative therapeutic targets. This collection of GO terms also helps shed light on the host mechanisms hijacked by SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 90%
“…Our GO clustering analyses detected clustering of great significance for annotations such as establishment of RNA localization, cell projection, lyase activity, cell cycle and more. These fall in line with the current literature which describes such disturbances upon SARS-CoV-2 infection 4042 and could also represent putative therapeutic targets. This collection of GO terms also helps shed light on the host mechanisms hijacked by SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, this assay setup is very similar to one recently shown to work as a specific and sensitive SARS-CoV-2 surrogate virus neutralization test based on antibody-mediated blockage of this same PPI (CoV-S-ACE2) (Tan et al, 2020). With this setup in our hands, we performed a preliminary screening of representative organic dyes from our in-house library plus a few compounds that are or have been considered of possible interest in inhibiting SAR-CoV-2 by different mechanisms of action, e.g., chloroquine, clemastine, and suramin (Colson et al, 2020;da Silva et al, 2020;Gordon et al, 2020;McKee et al, 2020;Xiu et al, 2020). Screening at 5 µM indicated that most have no activity and, hence, are unlikely to interfere with the S-protein -ACE2 binding needed for viral attachment.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have also revealed that suramin interferes with viral RNA synthesis by targeting viral RNA-dependent RNA polymerase (Albulescu et al, 2015;Mastrangelo et al, 2012). A recent study by de Silva et al demonstrated suramin inhibited SARS-CoV-2 replication in Vero E6 cells and reduced viral RNA in Calu-3 cells (da Silva et al, 2020). The authors proposed prevention of SARS-CoV-2 viral entry into cells as a mechanism of action.…”
Section: Discussionmentioning
confidence: 99%